A Randomized Prospective Time and Motion Comparison of Techniques to Process Autologous Fat Grafts. Issue 5 (27th April 2021) - Hanson, Summer E.; Garvey, Patrick B.; Chang, Edward I.; Reece, Gregory P.; Liu, Jun; Baumann, Donald P.; Butler, Charles E.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Time and motion studies provide a reliable methodology to quantify efficiency and establish recommendations for best practices in autologous fat grafting. The purpose of this study was to compare the rate of graft processing of three frequently used systems for graft preparation. Methods: The authors conducted a prospective randomized comparison of three methods to prepare adipose tissue for autologous fat grafting: an active filtration system (Revolve; LifeCell Corporation, Branchburg, N.J.), a passive filtration system (PureGraft 250; Cytori Therapeutics, San Diego, Calif.), and centrifugation. An independent observer collected data according to the study's behavioral checklist. The primary outcome measure was rate of adipose tissue processed. Results: Forty-six patients (mean age, 54 years; mean body mass index, 28.6 kg/m 2 ) were included in the study (15 per arm; one patient was included with intention to treat after a failed screening). The rate of adipose tissue preparation was greater for the active filtration system compared with the others (active filtration: 9.98 ml/min versus passive filtration: 5.66 ml/min versus centrifugation: 2.47 ml/min). Similarly, there was a significant difference in total grafting time (active: 82.7 ± 8.51 minutes versus passive: 152 ± 13.1 minutes, p = 0.0005; versus centrifugation: 209.9 ± 28.5 minutes, p = 0.0005); however, there was no difference in total operative time ( p = 0.82, 0.60). Conclusions: As the number of fat grafting procedures increases, there is interest in developing techniques to harvest, process, and inject fat to improve clinical outcomes and operative efficiency. The results of this study indicate that an active fat processing system is more time efficient at graft preparation than a passive system or centrifugation.